(untitled) (Revista Aspas, 2022)
The article seeks to situate the company Os Artistas Unidos within the transition process towards modern Brazilian theater and highlight the artistic profile it established at Teatro Copacabana during the years it remained installed there. It also intend to provide a brief context of the theatrical movement in Rio de Janeiro in the mid-twentieth century with the growing emergence of theater halls in the South Zone of the city, without, however, threatening the strength of the central region. This panorama is traced with texts by researchers in the history of Brazilian theater and records of testimonies from artists who worked throughout the aforementioned period.